2023
DOI: 10.1002/cpe.7637
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent credit scoring using deep learning methods

Abstract: Summary Credit scoring is one the most important parts of credit risk management in reducing the risk of client defaults and bankruptcies. Deep learning has received much attention in recent years, but it has not been implemented so intensively in credit scoring compared to other financial domains. In this article, stacked unidirectional and bidirectional LSTM (long short‐term memory) networks as a complex area of deep learning are applied in solving credit scoring problems for the first time. The proposed rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…In the case of the "Statlog (German Credit Data)" [22], the current study achieved an accuracy of 78.30%. While this accuracy is an improvement over some earlier studies, it falls short of the highest accuracy reported for this dataset, which was 88.89% by Gicić et al [14]. For "South German Credit " [23], this study achieved an accuracy of 77.80%.…”
Section: Related Studies Comparisoncontrasting
confidence: 69%
See 1 more Smart Citation
“…In the case of the "Statlog (German Credit Data)" [22], the current study achieved an accuracy of 78.30%. While this accuracy is an improvement over some earlier studies, it falls short of the highest accuracy reported for this dataset, which was 88.89% by Gicić et al [14]. For "South German Credit " [23], this study achieved an accuracy of 77.80%.…”
Section: Related Studies Comparisoncontrasting
confidence: 69%
“…The outcome of the experiments showed that the presented method achieved significant results in Australian credit score data and some progress on the German loan approval data. In Gicić et al [14], stacked unidirectional and bidirectional LSTM networks were applied to solve credit scoring tasks. The proposed model exploited the full potential of the three-layer stacked LSTM and BiLSTM architecture with the treatment and modeling of public datasets.…”
Section: Feature Selection Machine Learning and Credit Scoring: A Rev...mentioning
confidence: 99%
“…This architecture enables the automatic extraction of hierarchical features from data. In credit scoring, deep learning models, particularly convolutional neural networks (CNNs) and recurrent neural networks (RNNs), enhance the understanding of complex relationships within diverse datasets (Gicić et al, 2023). Deep learning excels when confronted with large and unstructured data, providing a robust framework for credit risk assessment.…”
Section: Ai Models In Credit Scoringmentioning
confidence: 99%
“…The development of rule-based and evolutionary models, such as the one proposed by Soui, Gasmi, Smiti, and Ghédira (2019), and the application of deep learning by Gicić, Ðonko, and Subasi (2023), have signiĄcantly improved the interpretability and accuracy of credit risk assessments. Mahajan et al (2022) contributed to the Ąeld by employing a Gaussian process-based approach for uncertainty handling in credit risk predictions.…”
Section: Advances In Credit Risk Modeling Techniquesmentioning
confidence: 99%